A primer in financial data management - Groot, Martijn (Academic Press, an imprint of Elsevier, 2017)
Title page; Table of Contents; Copyright; Foreword; Preface; Chapter 1: The Changing Financial Services Landscape; Abstract; 1.1. Data as the Lifeblood of the Industry; 1.2. Developments in Information Management; 1.3. The Supply Chain View of Data Management; 1.4. The Data Management Problem; 1.5. Outline of This Book's Chapters; Chapter 2: Taxonomy of Financial Data; Abstract; 2.1. Introduction; 2.2. Master Data Versus Transactional Data; 2.3. Structured Data Versus Unstructured Data; 2.4. Sources of Financial Information; 2.5. Data Creation Processes and Information Life Cycle. 2.6. Overview of Information Sets2.7. Conclusions; Chapter 3: Information as the Fuel for Financial Services' Business Processes; Abstract; 3.1. Steps in the Information Sourcing Process; 3.2. Data Management From the Instrument Lifecycle Perspective; 3.3. Data Management From the Trade Lifecycle Perspective; 3.4. Data Management From the Customer Interaction Perspective; 3.5. Data Management From the Regulatory Reporting Perspective; 3.6. Business Data Architecture; 3.7. Conclusions; Chapter 4: Challenges and Trends in the Financial Data Management Agenda; Abstract; 4.1. Introduction. 4.2. Changing Business Demands4.3. Changing Customer Demands; 4.4. Changing Regulatory Demands; 4.5. Supply Chain Developments; 4.6. Big Data and Big Data Management; 4.7. Conclusions and Future Outlook; Chapter 5: Data Management Tools and Techniques; Abstract; 5.1. Introduction: Technology Enablers; 5.2. Data Storage Models; 5.3. Big Data Technology for Financial Institutions; 5.4. Data Security; 5.5. Blockchain; 5.6. Cloud and Information Access; 5.7. IT Management and Buy Versus Build Considerations; 5.8. Conclusions and Future Outlook. Chapter 6: Data Management Processes and Quality Management Abstract; 6.1. Introduction: Metadata Classification and Data Management Processes; 6.2. Data Quality Fundamentals; 6.3. Data Quality Dimensions; 6.4. Data Quality Business Rules; 6.5. Quality Metrics: Information Management Supply Chain KPIs; 6.6. Exposing and Controlling Information Uncertainty; 6.7. Quality Augmentation and Remediation Processes: What to Do With KPIs?; 6.8. The Role of Data Standards; 6.9. Data Management Maturity Models; 6.10. ROI of Data Management Processes and Quality Management. 6.11. Conclusions and Future Outlook Chapter 7: Data Management Organization; Abstract; 7.1. Introduction: Changing Demands on Organizations; 7.2. Information Governance; 7.3. Organizational Approaches; 7.4. Outsourcing and Service Options in Data Management; 7.5. Change Management Programs for Shared Data Services; 7.6. Conclusions and Future Outlook; Chapter 8: What's Next?; Abstract; 8.1. Structural Changes in the Financial Services Industry; 8.2. The Supply Chain Perspective of Information Management; 8.3. Data Management Outlook; Bibliography; Index.